Pengaruh Salinitas terhadap Perkembangan Parasit pada Benih Gurami, Osphronemus goramy - Rahayu, Nani S.; Susanti, Dewi; Lantiani, Dwi; Wibowo, Sutopo A.; Diana, Roosita; Murwantoko, Murwantoko (Jurnal Perikanan Universitas Gadjah Mada, 2009)
Research was conducted to know the effect of salinity on the reduction of parasites in Gouramy (Osphronemus goramy). The Research was performed using completely Randomized design with 5 salinity treatments (water pond, water with salt concentration 0, 2, 4 dan 6 g/L) with 4 replications. The 5-7 cm of gouramy fingerling were reared as on treatments and the parasites were counted  using skin scrapping dan wet mount methods. Observation was performed every 3 day for 15 days on parasite intensity, prevalence, mortality, symptoms and water quality.The result showed that several parasites including Trichodina sp., Apiosoma sp., Ichthyophthirius sp., Oodinium sp., dan Henneguya sp were observed. The highest intensity and prevalence was found in Trichodina sp. The Salinity and lenght administration were significantly decrease number parasites.  Salinity treatments (2, 4 dan 6 g/L ) for 3 days could totally removing Trichodina sp. from fishes. Meanwhile the data of other parasite species were unsignificant due to the low level of its intensity and prevalence. Salinity administration in level 6 g/L could reduce mortality.